1H and 1T polymorphs, structural transitions and anomalous properties of (Mo, W)(S, Se)2 monolayers: first-principles analysis. (19th August 2015) - Singh, Anjali; Shirodkar, Sharmila N; Waghmare, Umesh V
Abstract: Among the 1H and 1T structures exhibited by monolayers of transition metal dichalcogenides, the group VI compounds MX2 (M = Mo, W and X = S, Se) largely occur in the 1H form. Recently, transformation of the 1H form to the 1T form with metallic electronic structure at high temperatures was demonstrated in MoS2 with Re substitution and electron irradiation by Lin et al (2014 Nat. Nanotechnology 9 391 ). Here, we use first-principles calculations to determine the energy landscape associated with the 1H to 1T phase transition, predict novel 1T structures and relate the observed by Lin et al (2014 Nat. Nanotechnology 9 391 ) intermediate structures to structural instabilities of the 1T structure of MX2 compounds. We show that the metallic centrosymmetric 1T (c 1T ) structure of these compounds is unstable with respect to dimerization or trimerization of metal atoms, leading to a competing metallic 1T form and ferroelectric semiconducting 1T form respectively. While the former is a more stable 1T form of MoSe2, WS2 and WSe2, the latter is a more stable 1T form of MoS2 exhibiting rich ferroelectric dipolar domain structure. In the vicinity of metal-semiconductor transitions, their semiconducting forms are shown to exhibit an anomalous response to electric fields. To facilitate the experimental verification of these subtle features of the 1T forms of MX2 monolayers, we present comparative analysis of their vibrational properties, and identify their Raman and infra-red spectroscopic signatures.